ChemInform Abstract: Gold‐Catalyzed Addition of N‐Hydroxy Heterocycles to Alkynes and Subsequent 3, 3‐Sigmatropic Rearrangement. Issue 25 (3rd June 2013) - Kumar, Manish; Scobie, Martin; Mashuta, Mark S.; Hammond, Gerald B.; Xu, Bo
Abstract The two‐step procedure represents an efficient oxygen transfer protocol which incorporates a nucleophilic oxygen atom into an alkyne group.